Fanatisme dan Kohesi Kelompok dalam Agresi Konser KPop: Fanaticism and Group Cohesion in KPop Concert Aggression - Denysa Firda Hanim; Effy Wardati Maryam (Academia Open, 2025)
General Background: The rapid growth of K-Pop fandom in the digital era has intensified collective fan engagement, particularly among young women, creating complex social dynamics within concert settings. Specific Background: Incidents of verbal and physical aggression during K-Pop concerts in Indonesia indicate that emotional attachment and strong group bonds may shape behavioral responses among fans. Knowledge Gap: Previous studies have rarely examined the combined association of fanaticism and group cohesiveness with aggressiveness among female K-Pop fans who have attended live concerts. Aims: This study aims to examine the relationship between fanaticism and group cohesiveness with aggressiveness among K-Pop fans who have watched their idols’ concerts. Results: Using a quantitative correlational design with 159 respondents from K-Pop communities in Sidoarjo, the findings reveal a significant simultaneous relationship (F = 38.374; p < 0.05), with fanaticism contributing 22.7% and group cohesiveness 14.3% to aggressiveness. Novelty: The study focuses specifically on female concert attendees, addressing a limited empirical area within social and behavioral psychology of fandom. Implications: These findings highlight the importance of emotional regulation and group dynamics management in large-scale fan gatherings to reduce aggressive tendencies. Keywords: Fanaticism, Group Cohesiveness, Aggressiveness, KPop Fans, Concert Behavior Key Findings Highlights: Fan attachment level shows the strongest statistical contribution to aggressive tendencies. Collective bonding within fandom communities is positively associated with hostile actions. Simultaneous correlation confirms both predictors significantly relate to behavioral escalation during live performances.